Effects of Quark Interactions on Dynamical Chiral Symmetry Breaking by a Magnetic Field - Hiller, B.; Osipov, A.A.; Blin, A.H.; Providência, João da (Symmetry, Integrability and Geometry: Methods and Applications, 2008)
It is shown how the strong interaction dynamics of a multi-quark Lagrangian affects the catalysis of dynamical symmetry breaking by a constant magnetic field in (3+1) dimensions. Attention is drawn to the local minima structure of the theory.